Mengungkap Peran Vital Nyanyian Nutu Ku Lesung dalam Tradisi Desa Dokan - Mei Sonni Sinaga (Departement of Mathematics Education, 2025)
This research aims to conduct an ethnomusicological investigation into the Nutu ku Lesung song, with a focus on its structure, meaning, and function within the context of the agricultural ritual practiced by the Karo people in Dokan Village. This study analyzes the Nutu ku Lesung song through an ethnomusicological lens. By analyzing the text, melody, and sociocultural context, this research strives to understand the significance and purpose of the song within the Dokan Village community. Data collection for this study was conducted through audio recordings, transcription, and textual analysis. The findings reveal that the Nutu ku Lesung song possesses a distinct melodic structure and lyrics laden with symbolic meaning. The song serves not only as an aesthetic expression but also as a vehicle for conveying social and moral values within the community. This research employed a descriptive qualitative research methodology. The entire community of Dokan Village constituted the population for this study, with a sample size of 10 participants actively involved in the Nutu ku Lesung activity. Through interviews with these 10 informants, the study elucidates that the Nutu ku Lesung song is an integral component of the Kerja Tahun (annual labor) ceremony in Dokan Village. This activity, historically performed collectively by the Singuda-nguda (youth), is now more commonly performed by the Nini-nini (elders). The pounded rice is used to produce cimpa flour, a traditional food central to the celebratory event. The shift in roles within this activity underscores the dynamics of tradition preservation in the face of societal change.